Viagem de volta ao passado : a (des)proteção social na garantia do direito à convivência familiar e comunitária de crianças e adolescentes - Dorneles, Alexia (2018)
The purpose of this dissertation is to analyze how the care of the families of children and adolescents hosted institutionally and assisted by the Social Assistance Policy in a municipality of the metropolitan region of Porto Alegre / RS has been constituted in the perspective of guarantee the right to family and community living, in order to contribute with subsidies in the qualification of this public policy. This is a qualitative research, developed through documentary research in ten (10) judicial processes, concerning the institutional reception of children and adolescents, which were in process in the Juiz de Infância e Juventude (JIJ), in the municipality of the metropolitan region of Porto Alegre, in the years 2016 and 2017, as well as in documents that give guidelines for institutional reception in Brazil, which deal with the right to family and community coexistence of children and adolescents: National Plan for the Promotion, Protection and Defense of the Right of Children and Adolescents to Family and Community Coexistence (2006a); Technical Guidelines for Reception Services for Children and Adolescents (2009) and Law No. 12.010, of August 3, 2009, which provides for Adoption (2009). Empirical research was also developed through interviews with seven (7) professionals who are included in the Social Assistance Policy and in the Tutelary Council of said municipality. In this way, through this study, it was observed that the reasons that contribute to the institutional reception of children and adolescents refer to the situation of social vulnerability, poor housing conditions, neglect and intra-family violence. In addition, some families were in a situation of unemployment and informal work, which also corroborated for the weakening of the bonds. In this way, it is understood that, in the present times, a journey back to the past is lived, since there is a regression in the realization of the rights of childhood and adolescence, because one advances in the legal context, however, through the advance of the neoliberal offensives and conservative, returns to the minorist logic in meeting the demands presented by children and adolescents. Also, it is understood that the legal argument has been constructed through perspectives of the moralization of the social question. In this way, a cycle is created, where the family suffers the impact of the capital dynamics, but is blamed, which corroborates for the institutional reception and the loss of family power. Thus, it has been observed that families that have their children institutionally are exposed to a context of (de) social protection. Among the challenges identified for the realization of the right to family and community coexistence of children and adolescents, the current context of precariousness of the Social Assistance Policy of the municipality under investigation is highlighted, since this public policy is surrounded by manifestations of the process of precariousness of the such as outsourcing and the high turnover of professionals, mid-level and higher. In addition, it was observed that there is a lack of investment in the service that offers basic social protection, which, together with the manifestations of the precarious work process, contributes to the discontinuity of care and follow-up of families. In addition, through this study, it was observed that the right to family and community coexistence of children and adolescents who are institutionally welcomed has been effected by violating the right to live with the family of origin. Regarding the possibilities, it is understood that, by means of a public tender, stability would be guaranteed to the professionals, for the development of intersectoral work. In addition, it is necessary to invest more in social policies - in this case in the Social Assistance Policy, with human and material resources, in order to develop a work based on integral protection, contributing with the families in facing the expressions of the social question; in the reduction of the chances of referral of children and adolescents to the institutional reception, as well as the length of stay of these subjects in the host institutions, with a view to the realization of the right to family and community coexistence.